Four decades of academic research on product diversification-performance relationship: analysis and foresight - Mehmood, Khawaja Khalid; Abdullah, Haim Hilman (Inderscience Publishers, 2017)
This paper presents a critical review of past research on the relationship of product diversification to performance and suggests avenues for future research. Several perspectives provide rationalization for pursuing product diversification strategy but academic research on the relationship produced inconsistent findings. Likewise, supremacy of related diversification against unrelated diversification also remains an unsolved mystery. The deployment of different product diversification measurement techniques, performance ratios, and application of multiple research designs contributed to the body of knowledge but also added to inconsistencies on the topic. Admitting the complexity of this topic, some researchers adopted contingency perspective of the relationship and contributed to this research area by studying the relationship of product diversification to performance through use of moderators. Future researchers need to test certain other crucial moderators in the context of this relationship along with ensuring careful selection of diversification measurement techniques and performance indicators.